Learning to find the meaning of life as educational pillar innovation beyond the unesco concept - Suhifatullah, M. I. (ARKA INSTITUTE, 2022)
Education is essentially an effort to actualize and develop various potential student personalities, both related to physical and mental aspects. In order for education to produce outputs that have superior competence in dealing with various problems and realities of life, UNESCO formulates 4 (four) pillars of education as a support for the education system, namely: (1) learning to know; (2) learning to do; (3) learning to be; and 4) learning to live together. However, according to the author, these pillars are not sufficient to support one's personality in achieving happiness. Because happiness is closely related to the ability to give true meaning to the reality of life that comes from spiritual intelligence. On that basis, through this literature study the authors conducted an analysis of 1 (one) pillar of education, namely learning to find the meaning of life, as an innovation pillar of education outside the UNESCO concept. This study is expected to complement and perfect the pillars of education into 5 (five) pillars, namely; (1) learning to know; (2) learning to do; (3) learning to be; (4) learning to live together; and (5) learning to find the meaning of life.